Comparison of Social Development of Athlete (Team and Individual Disciplines) and Non-Athlete Students of Farhangian University - Morteza Pourazar; Morteza Homayounnia Firouzjah (University of Tehran, 2022)
Introduction: Sport is an important part of students' life. The social development of athletes could be different based on their gender and type of sport. The present study aimed to compare the social development of athletes (team and individual sports disciplines) and non-athlete students of Farhangian University.Methods: In a descriptive cross-sectional survey research, 2000 male and female students of Farhangian University of Mazandaran province were recruited as a statistical population. 300 students were selected using the cluster random sampling method. Witsman's Social Development Questionnaire (1990) was used as the research instrument.  To analyze the data, a two-way analysis of variance and Tukey's post hoc test were used.Results: Based on the results of the two-way analysis of variance, significant results were found for the main effect of gender and group variables. However, the interaction effect of group and gender was not significant. The social development of female students was higher compared with male students. Based on the results of Tukey's post hoc test, athletes had significantly higher social development than non-athletes. Although the social development of athletes in individual sport discipline had a higher mean than the team athletes, the difference was not significant.Conclusion: Considering the higher social development of athletes compared with non-athletes and also, almost identical social development scores for both groups of athletes (team and individual sports disciplines), it is suggested that coaches foster a supportive environment by emphasizing the importance of equality of each athlete to provide the basis for social development among all people.